2021
DOI: 10.1097/ico.0000000000002849
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Scleral and Limbal Inflammatory Necrosis After Adjuvant Miltefosine for Recalcitrant Acanthamoeba Keratitis

Abstract: Purpose:The purpose of this study was to report a retrospective case series of anterior scleral and limbal inflammatory necrosis after adjuvant miltefosine for recalcitrant Acanthamoeba keratitis (AK).Methods:A case series and literature review.Result:Four eyes of 3 patients with recalcitrant AK developed anterior scleral and limbal inflammatory necrosis with significant scleral-limbal thinning after treatment with miltefosine. The average age was 38 years, and the average duration of infection before miltefos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…On the one hand, Vemuganti et al 4 reported parasite-mediated cytolysis and phagocytosis of corneal cells with destructive granulomatous inflammation in cases of worsening AK. On the other hand, de la Presa et al 9 recently reported a case series demonstrating significant scleral inflammation after miltefosine treatment for AK that had previously spared the sclera. Thus, both inflammatory and infectious components may contribute to clinically observed scleritis.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Vemuganti et al 4 reported parasite-mediated cytolysis and phagocytosis of corneal cells with destructive granulomatous inflammation in cases of worsening AK. On the other hand, de la Presa et al 9 recently reported a case series demonstrating significant scleral inflammation after miltefosine treatment for AK that had previously spared the sclera. Thus, both inflammatory and infectious components may contribute to clinically observed scleritis.…”
Section: Discussionmentioning
confidence: 99%
“…The main side effects noted were nausea and vomiting, and elevated liver enzymes [69]. Several clinicians have reported increased corneal inflammation leading to corneal and scleral melts after initiating miltefosine that required topical and/or oral steroids [69][70][71]. In addition, a recent case report described an occurrence of miltefosine-associated keratopathy that likely occurred from extracellular formation of cholesterol crystals [72].…”
Section: Therapy For Acanthamoeba Keratitismentioning
confidence: 99%